Influence of weather parameters on foliar diseases of sesame: Influence of weather parameters on foliar diseases of sesame - K N GUPTA,; JAINPAL RATHOR,; RAJANI BISEN,; SURBHI JAIN, (Journal of Oilseeds Research, 2023)
Three years field experiment was conducted on sesame during Kharif 2015 to 2017 to find out the effect of climate factor and management for foliar disease in sesame. In this experiment, i.e. three sesame varieties, JTS-8, TKG-21 and GT-10 were sown with two treatments protected and unprotected. The severity of powdery mildew and Alternaria and Cercospora was recorded at weekly intervals using 0 - 5 grade scale. The disease severity was correlated with the weather parameters. Correlation of diseases with the weather parameters indicated that Alternaria and Cercospora severity was positively correlated with Relative humidity observed during morning and evening. Similarly, the powdery mildew was also positively correlated with relative humidity.